Pengaruh Komunikasi, Motivasi dan Kerjasama Tim Terhadap Peningkatan Kinerja Karyawan - Eva Silvani Lawasi; Boge Triatmanto (Jurnal Manajemen dan Kewirausahaan, 2017)
The purpose of this study are : 1) to know and analyze the influence of communication, motivation, and team cooperation on employee performance. 2) to know and analyze the variable that has dominant influence to employee performance. The data obtained in this study is the primary data by distributing questionnaires to the respondents. Analyzed data uses multiple linear regression model.. The results of this study prove that, 1) communication has a positive and significant effect on the improvement of employee performance. 2) Motivation has a positive and significant effect to the improvement of employee performance. 3) Team cooperation doesn’t have a significant effect to the improvement of employee performance and 4) Communication has the dominant influence in improving employee performancehttps://doi.org/10.26905/jmdk.v5i1.1313